2013
DOI: 10.1002/jbm.a.34688
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal biofilm growth on smooth and porous titanium coatings for biomedical applications

Abstract: Implant-related infections are a serious complication in prosthetic surgery, substantially jeopardizing implant fixation. As porous coatings for improved osseointegration typically present an increased surface roughness, their resulting large surface area (sometimes increasing with over 700% compared to an ideal plane) renders the implant extremely susceptible to bacterial colonization and subsequent biofilm formation. Therefore, there is particular interest in orthopaedic implantology to engineer surfaces tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
84
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 49 publications
(69 reference statements)
4
84
1
2
Order By: Relevance
“…Singh et al [68] demonstrated that modifying surface roughness (Figures 7 [69] and 8) of a material at the nanoscale level could provide antibacterial properties. Surface characteristic modification has been shown to interfere with osseointegration of the implants, challenging its clinical application [70] . Other studies have shown that certain pathogens are able to adhere, proliferate, and form biofilms more readily on rough surfaces.…”
Section: Modified Surface Characteristicsmentioning
confidence: 99%
“…Singh et al [68] demonstrated that modifying surface roughness (Figures 7 [69] and 8) of a material at the nanoscale level could provide antibacterial properties. Surface characteristic modification has been shown to interfere with osseointegration of the implants, challenging its clinical application [70] . Other studies have shown that certain pathogens are able to adhere, proliferate, and form biofilms more readily on rough surfaces.…”
Section: Modified Surface Characteristicsmentioning
confidence: 99%
“…Hydrophobic bacteria, such as S. epidermidis, are known to detach more easily and form less biofilm on a hydrophilic surface. [27][28][29] We therefore suggest that increased hydrophilicity, induced by nanotopography, is a factor contributing to the lower amounts of live bacteria seen on the nanostructured surfaces in our experiments. Moreover, a small decrease in live bacteria was found when increasing the density of nanoparticles from 17% to 28%.…”
Section: Surface Nanotopography Influences Bacterial Adhesion and Biomentioning
confidence: 99%
“…Many factors will affect bacterial adhesion to a prosthetic surface such as the material's chemical composition, electric charge, hydrophobicity, and surface roughness [5], among others. Multifilament materials [5] and, surface roughness especially, determine microbial adhesion properties such that surface irregularities will favour the adhesion and deposition of biofilms [6] while smooth surfaces will be less susceptible to microbial adhesion [7]. The porosity of the biomaterial surface also conditions its bioreceptivity [8].…”
Section: Introductionmentioning
confidence: 99%